Rett syndrome: a review of clinical manifestations and therapeutic approaches - Bricker, Katelyn; Vaughn, Bradley V. (Frontiers in Sleep, 2024)
Rett syndrome (RTT) is a severe X-linked dominant neurodevelopmental disorder predominantly affecting females (Tascini et al., 2022) and over 90% of these patients mutations linked to the methyl-CpG-binding protein 2 (MeCP2) gene (Zoghbi 2005, Weaving et al., 2005). Although the syndrome is well noted for the classic repetitive hand motion with decline in speech, patients may have a wide range of cognitive and motor impairments. Typical comorbidities in RTT are characterized by poor growth, seizures, disrupted sleep, hyperventilation, breath holding spells, feeding difficulties, scoliosis, and behavioral issues (Gold et al., 2018). This paper aims to provide a brief overview of RTT, focusing on the clinical features of sleep and epilepsy, effects on childhood development, and available emerging treatment options. Sleep disturbances, epilepsy, and developmental regression can have profound effects on the quality of life in affected individuals. Current management strategies focus on a multidisciplinary approach to address symptoms and enhance overall well-being of individuals with RTT.